Targeted Sister Chromatid Cohesion by Sir2 - Wu, Ching-Shyi (Public Library of Science, 2011)
The protein complex known as cohesin binds pericentric regions and other sites of eukaryotic genomes to mediate cohesion of sister chromatids. In budding yeast Saccharomyces cerevisiae, cohesin also binds silent chromatin, a repressive chromatin structure that functionally resembles heterochromatin of higher eukaryotes. We developed a protein-targeting assay to investigate the mechanistic basis for cohesion of silent chromatin domains. Individual silencing factors were tethered to sites where pairing of sister chromatids could be evaluated by fluorescence microscopy. We report that the evolutionarily conserved Sir2 histone deacetylase, an essential silent chromatin component, was both necessary and sufficient for cohesion. The cohesin genes were required, but the Sir2 deacetylase activity and other silencing factors were not. Binding of cohesin to silent chromatin was achieved with a small carboxyl terminal fragment of Sir2. Taken together, these data define a unique role for Sir2 in cohesion of silent chromatin that is distinct from the enzyme's role as a histone deacetylase.